Testicular thermoregulation in Bos indicus, crossbred and Bos taurus bulls: relationship with scrotal, testicular vascular cone and testicular morphology, and effects on semen quality and sperm production - Brito, LFC; Silva, AEDF; Barbosa, R. T.; Kastelic, J. P. (Elsevier B.V., 2004)
Mechanisms of testicular thermoregulation, the relationship of scrotal, testicular vascular cone (TVC), and testicular morphology with thermoregulatory capability, and their effects on semen quality and sperm production were studied in 20 Bos indicus, 28 crossbred, and 26 Bos taurus bulls. The ratio of testicular artery length and volume to testicular volume were larger (P < 0.05) in B. indicus and crossbred bulls than in B. taurus bulls (1.03 and 0.94 cm/cm(2). versus 0.48 cm/cm(3); 0.034 and 0.047 ml/cm(3) versus 0.017 ml/cm(3), respectively). Testicular artery wall thickness (average 192.5, 229.0, and 290.0 mum, respectively) and arterial-venous blood distance in the TVC (average 330.5, 373.7, and 609.4 pm, respectively) were smallest in B. indicus, intermediary in crossbred, and greatest in B. taurus bulls (P < 0.05); the proximity between arterial and venous blood was consistent with the estimated decrease in arterial blood temperature after passage through the TVC (5.9, 5.0, and 2.9 degreesC, in B. indicus, crossbred, and B. taurus bulls, respectively). In crossbred and B. taurus bulls, there was a positive top-to-bottom scrotal temperature gradient and a negative testicular subtunic temperature gradient. However, in B. indicus bulls, both scrotal and testicular subtunic temperatures gradients were positive. Differences in the vascular arrangement, characteristics of the artery (e.g. wall thickness) or thickness of the tunica albuginea may have affected the testicular arterial blood and subtunic temperatures in B. indicus bulls. Better testicular thermoregulatory capability was associated with increased scrotal shape (pendulosity), testicular artery length and volume, and top-to-bottom gradient of the distance between the artery wall and the veins in the TVC. Increased semen quality was associated with increased testicular volume and scrotal subcutaneous (SQT) temperature gradient, and with decreased scrotal surface and testicular temperatures. Increased sperm production was associated with increased testicular artery volume, testicular volume, and SQT temperature gradient, and with decreased testicular artery wall thickness, scrotal circumference (SC), and scrotal surface, testicular subtunic, and epididymal temperatures. In conclusion, morphology of the TVC may contribute to the greater resistance of B. indicus bulls to high ambient temperatures by conferring a better testicular blood supply and by facilitating heat transfer between the testicular artery and veins. Testicular thermoregulation was associated with opposing scrotal and testicular subtunic temperatures gradients only in crossbred and B. taurus bulls. Scrotal, TVC, and testicular morphology influence testicular thermoregulatory capability and were associated with differences in semen quality and sperm production. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: bull; testes thermoregulation; scrotum; testicular vascular cone; semen